1993
DOI: 10.1037/0882-7974.8.3.463
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional beliefs and attitudes about sleep among older adults with and without insomnia complaints.

Abstract: This study examined the beliefs and attitudes about sleep among 145 older adults. Ss were either chronic insomniacs (n = 74) or self-defined good sleepers (n = 71). They rated their level of agreement or disagreement (visual analog scale) with 28 statements tapping various beliefs, expectations, and attributions about several sleep-related themes. The results showed that insomniacs endorsed stronger beliefs about the negative consequences of insomnia, expressed more hopelessness about the fear of losing contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
273
4
12

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(307 citation statements)
references
References 15 publications
18
273
4
12
Order By: Relevance
“…Worries about sleep, physical health, or other stressors may increase both cognitive and physiologic arousal. 28 …”
Section: Cognitionsmentioning
confidence: 99%
“…Worries about sleep, physical health, or other stressors may increase both cognitive and physiologic arousal. 28 …”
Section: Cognitionsmentioning
confidence: 99%
“…A meta-analysis by Pallesen, Nordhus, and Kvale (1998) showed that behavioral treatments resulted in significant and long-lasting improvements in the sleep patterns of older insomniacs. Specific behavioral treatments have been reported, including sleep hygiene, which consists of educating those with sleep problems how to engage in healthy sleep habits (e.g., Martin et al, 2000), and sleep restriction, which reduces the amount of time a person is allowed to spend in bed and so avoids the frustration that is believed to perpetuate insomnia (e.g., Morin et al, 1993). CBT models often incorporate the previously listed techniques in combination with cognitive restructuring so that dysfunctional beliefs about sleep are corrected (e.g., Morin et al, 1993).…”
Section: Sleep Disordersmentioning
confidence: 99%
“…Specific behavioral treatments have been reported, including sleep hygiene, which consists of educating those with sleep problems how to engage in healthy sleep habits (e.g., Martin et al, 2000), and sleep restriction, which reduces the amount of time a person is allowed to spend in bed and so avoids the frustration that is believed to perpetuate insomnia (e.g., Morin et al, 1993). CBT models often incorporate the previously listed techniques in combination with cognitive restructuring so that dysfunctional beliefs about sleep are corrected (e.g., Morin et al, 1993). Direct comparisons with medications for sleep are rare; however, Morin and colleagues (1999) found that CBT and pharmacological treatments (combined and alone) improved sleep, although those in the medication-alone group did not maintain their therapeutic gains at 2-year follow up.…”
Section: Sleep Disordersmentioning
confidence: 99%
“…Unrealistic positive beliefs about the soundness of sleep can lower the threshold for complaining about insomnia. This concern is particularly warranted for the elderly (Morin et al, 1993) because sleep normally changes in a negative direction with advancing age. Increased sleep onset latency (SOL) and increased wake time after sleep onset (WASO) constitute normal age-related changes in sleep (Miles & Dement, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…This may indicate that patients whose complaints are based on unrealistic sleep expectations, do not suffer from any sleep disorder. However, faulty appraisals may heighten emotional arousal and turn what are normal changes in sleep patterns into a clinical problem (Morin et al, 1993). It is also important to remember that subjective complaints and objective, that is polysomnographic (electroencephalogram, electroocculogram and electromyogram) recordings of sleep not always converge (e.g.…”
Section: Introductionmentioning
confidence: 99%